From Outreach to Co-Creation: Redefining Community Service through Collaborative Knowledge Production - Joseph, John; Charles, David; Denis, Samuel (Journal Ligundi of Community Service, 2025)
Traditional models of community service have often focused on service delivery, where external organizations provide resources to communities in need. However, this approach often overlooks the long-term empowerment and active participation of communities in shaping their own development. In recent years, the concept of co-creation has emerged as a transformative approach, emphasizing collaborative knowledge production between service providers and community members. This study explores how community service can be redefined through co-creation, with a focus on how this participatory approach fosters sustainable social transformation. The research employs a mixed-methods design, combining case study analysis with participatory action research (PAR). The study examines communities that transitioned from service delivery models to co-creation practices, analyzing the impacts on community engagement, empowerment, and social outcomes. Findings indicate that co-creation significantly enhances community ownership, satisfaction, and social cohesion. Additionally, communities involved in co-created initiatives reported more sustainable and contextually relevant solutions. This research concludes that co-creation is a key driver for redefining community service, promoting long-term transformation through collaborative knowledge production. The study offers a framework for implementing co-creation in community service, providing valuable insights for policymakers, community leaders, and development practitioners.